Methodological advances in diatom research for aquatic biomonitoring and water quality evaluation - Sindhwal, Sneha; Rinku; Saxena, Abhishek; Navarro-Márquez, Mireya; Parra-Saldívar, Roberto; Tiwari, Archana (Springer, 2026)
Diatoms, a unique class of microalgae, play a pivotal role in global ecosystems due to their photosynthetic capabilities and adaptability to diverse aquatic environments. Composed of opaline silica, they serve as sensitive indicators for water quality monitoring. This review covers various diatom research techniques, including sampling and isolation. It highlights methods for different substrata, such as epiphyton, epipelon, and epipsammon, as well as traditional isolation approaches like agar plate methods and serial dilution. Automation techniques, such as flow cytometry (FACS), are also discussed. The review emphasizes the potential of diatoms for pollutant removal, particularly heavy metals, and presents various diatom-based indices for water quality assessment. Future research is encouraged to refine isolation techniques, enhance the effectiveness of indices, and explore biochemical pathways that could improve diatoms’ bioremediation capabilities, thereby fully leveraging their potential for environmental monitoring and remediation.
Keywords: 31 Biological Sciences; 3103 Ecology; Microbiology; 3107 Microbiology; Axenic Cultures; Bioremediation; Diatom-Based Indices; Isolation; Sample Collection; Diatoms; Water Quality; Environmental Monitoring; Water Pollutants, Chemical; Biodegradation, Environmental; Metals, Heavy; Ecosystem